Stability and thermal analysis of a single-phase natural circulation looped parabolic trough receiver. (August 2022) - Nakul, S.; Arunachala, U.C.
Graphical abstract: Highlights: Stability maps generated show high degree of instability in the square loop. Combination of loop tilt and orifice is effective in restraining instability. Effect of heat flux pattern on the system performance is insignificant. Feasibility of a natural circulation loop in parabolic collectors is explored. Abstract: The sustainability and reliability of solar parabolic trough technology can be enhanced by introducing a natural circulation loop. The configuration that suits better is horizontal heater horizontal cooler, which is the most efficient but least stable loop. Hence, as an effort towards the evolution of natural circulation looped collector, 3D computational analysis of a 70 mm uniform diameter square loop (Dowtherm A as the heat transfer fluid) is done with uniform and non-uniform heat flux (SolTrace based) as well as different instability restraining techniques. Prior to the analyses, the stability maps were generated and validated, which predicts high level of instability. Later, the validated computational model is used for parametric analyses, which includes heat flux pattern, loop tilt, use of orifice, and combination of tilt and orifice. Since the loop geometry is highly unstable (ratio of loop length to diameter is 57), the stable operation is observed only with high tilt (θ = 45°), low beta ratio (β = 0.25) and combinations of tilt and orifice (β (0.50) + θ (15°) and β (0.50) + θ (30°)). However, the latter method is suggested for trough application as the former two versions are impractical. Further, the heat load analysis with uniform and non-uniform flux designated insignificant variation in system performance. Since the loop is effective with restraining techniques and its performance is on par with the conventional trough system (predicted by the analytical model), an effort towards implementation of natural circulation loop in parabolic trough technology is prolific.